Adaptive Terminal-Integral Sliding Mode Force Control of Elastic Joint Robot Manipulators in the Presence of Hysteresis - Taher Azar, Ahmad (2019)
Part of the Advances in Intelligent Systems and Computing book series (AISC, volume 1058)